Microelectronic packaging for retinal prostheses. - Rodger, D.C.
An innovative parylene-based high-density chip-level integrated interconnect (CL-I2) packaging system for retinal implants id discussed. The implications of this CL-I2 technology for retinal prosthesis packaging effort are far-reaching. This technology obviates the need for a technician to create electrical and mechanical connections one by one. Instead, the technology is limited only by standard photolithography and standard microfabrication techniques, providing the capability for a reduction of an order of magnitude or more in the center-to-center pad distances that can be accommodated in the process. High-density electrode arrays are thereby feasible, because the fabrication process places no limit on the number of output pads that can reasonably be connected to the array.
Keywords: High-density electrode arrays; Innovative parylene-based high-density chip-level integrated interconnect packaging system; Microelectronic packaging; Microfabrication; Photolithography; Retinal implants; Retinal prostheses